Potential use of albumin and neutrophil‐to‐lymphocyte ratio to guide the evaluation and treatment of cancer‐related depression and anxiety. Issue 2 (4th September 2021) - McFarland, Daniel C.; Applebaum, Allison J.; Bengtsen, Erik; Alici, Yesne; Breitbart, William; Miller, Andrew H.; Nelson, Christian
Abstract: Background: Depression and anxiety are common and associated with inflammation in patients with cancer. Inflammatory indices such as albumin and neutrophil‐to‐lymphocyte ratio (NLR) obtained from metabolic panels and complete blood counts should be available for mental health professionals treating anxiety and depression at cancer centers. We hypothesized that albumin and NLR extrapolated from non‐mental health oncology appointments would be associated with anxiety and depression and drawn close enough to psychiatry visits to be useful for the psycho‐oncologist. Materials & Methods: Depression and anxiety were evaluated in patients ( n  = 97) referred to a cancer center psychiatric service for depression using the Patient Health Questionnaire‐9 and General Anxiety Disorder‐7. Albumin concentration and NLR were assessed for timing and correlation strength with anxiety and depression by setting (localized/metastatic cancer). Results: Most patients (96%) had albumin or NLR available at any time point of which 45% were drawn within one week of the psychiatric appointment. No significant correlations were noted when evaluating localized cancer or NLR exclusively. For patients with metastatic cancer, anxiety and depression were correlated with albumin at any time point ( r  = −0.28, p  < 0.05; r  = −0.40, p  < 0.01, respectively) and within a week of psychiatry appointment ( r  = −0.40, p  < 0.05; r  = −0.68, p  < 0.001, respectively). Albumin evaluated within a week predicted 32% of depression score variance ( β  = −0.63, p  = 0.002). Hypoalbuminemia (<3.8 g/ul) was associated with anxiety ( χ 2 = 4.43, p  = 0.04) and depression ( χ 2 = 11.06, p  = 0.001). Conclusion: Hypoalbuminemia in patients with metastatic cancer may help establish the presence or persistence of anxiety, depression, treatment refractoriness, and the use of inflammation in cancer‐related psychological symptom management.